Second-Order Sliding Mode Guidance Law considering Second-Order Dynamics of Autopilot - Kuanqiao Zhang; Suochang Yang (Journal of Control Science and Engineering)
Aiming at the requirement that some missiles need to meet certain impact angles when attacking targets, we consider the second-order dynamic characteristics of autopilot, thereby proposing a second-order sliding mode guidance law with impact angle constraint. Firstly, based on the terminal sliding mode control, we design a fast nonsingular terminal sliding mode guidance law with impact angle constraint. Based on the second-order sliding mode control, a second-order sliding mode guidance law with impact angle constraint is proposed. We have proved its finite time convergence characteristics and presented the specific convergence time expression. Subsequently, the dynamic characteristics of the autopilot are approximated to the second-order link. Combined with the dynamic surface control theory, we proposed a second-order sliding mode guidance law considering the second-order dynamic characteristics of the autopilot and proved its finite-time convergence characteristics. Finally, the effectiveness and superiority of the proposed guidance law are verified by comparative simulation experiments.